Effects of agitation rate and dissolved oxygen on xylose reductase activity during xylitol production at bioreactor scale (2021)
The study of xylose reductase (XR) - one of the key enzymes in the production of xylitol - is important in the fermentation process to have maximum efficiency in the bioconversion of xylose to xylitol in lignocellulosic hydrolysate. The aim was to evaluate the effect of agitation rate and dissolved oxygen at 7 L bioreactor scale on the production of xylose reductase (XR) from Candida tropicalis during the bioconversion of xylose into xylitol in the non-detoxified oil palm empty fruit bunch (OPEFB) hydrolysate. The highest xylose consumption (95.5%) and the maximum xylitol production (5.46 g.L-1) were presented under 30% dissolved oxygen and 50 rpm. The maximum XR activity (0.646 U mg-1 protein) was obtained after 144 h of fermentation and at the same conditions of dissolved oxygen and agitation rate mentioned above. The oxygen availability influences the XR activity of C. tropicalis and the xylitol production, observing a xylitol yield factor (YP/S) of 0.27 g.g-1 and volumetric productivity (QP) of 0.33 g.L-1 h-1. At lower dissolved oxygen regardless of the agitation conditions evaluated, an increase in xylitol production was evidenced.